2014
DOI: 10.1007/s00228-014-1746-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of off-label drug uses in hospitals: a multicentric prospective study

Abstract: PurposeThe study aims to assess the clinical evidence, outcome and cost of off-label use of medicines in the hospital setting.MethodsA multicentric prospective cohort study of patients treated with off-label medicines was carried out in five tertiary hospitals from May 2011 to May 2012. Information on clinical characteristics of patients, drugs, outcomes and costs was collected. Patients were followed up to 6 months, and information was assessed by reviewing clinical records and interviewing physicians.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Among targeted therapies, rituximab is the agent that probably carries the greatest potential for off-label indications mostly beyond oncology. Indeed, a Spanish prospective investigation reported that rituximab was the most frequently used agent off-label (21.1%) among 232 drugs (considering all therapeutic classes) in 5 tertiary hospitals during one year (2011-2012) [14] . In addition, a prospective Australian national study found that offlabel use of rituximab covers 63 different diagnosis with 89% of off-label use outside oncology in the year 2012 [15] .…”
Section: Prevalence and Clinical Evidencementioning
confidence: 99%
“…Among targeted therapies, rituximab is the agent that probably carries the greatest potential for off-label indications mostly beyond oncology. Indeed, a Spanish prospective investigation reported that rituximab was the most frequently used agent off-label (21.1%) among 232 drugs (considering all therapeutic classes) in 5 tertiary hospitals during one year (2011-2012) [14] . In addition, a prospective Australian national study found that offlabel use of rituximab covers 63 different diagnosis with 89% of off-label use outside oncology in the year 2012 [15] .…”
Section: Prevalence and Clinical Evidencementioning
confidence: 99%
“…Recently, a multicentric prospective cohort study of 226 patients treated with off-label medicines was carried out in five tertiary hospitals from May 2011 to May 2012 [9]. Omalizumab was used in 6 % of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been noted that healthcare professionals commonly prescribe medicines off-label with levels of evidence considered to be low. This is principally problematic because off-label use with inadequate strong scientific evidence may be associated with higher rates of adverse events that may harm the patient (2)(3)(4) . Off-label prescribing is not certainly bad.…”
Section: Introductionmentioning
confidence: 99%